Innovative Modernization Management of High-Tech and Knowledge-Intensive Industries of Russian Economy - S. S. Demin; E. V. Dzhamay; L. M. Putyatina (Управление)
In the article a new economic category “innovative modernization” reflecting system technical and technological and organizational and economic updating of high-tech and knowledge-intensive industries of economy of Russia is offered and proved. Authors opened the essence and the content of the concept “innovative modernization”, various versions of long-term forecasts of development of economy of Russia in relation to high-tech and knowledge-intensive industries are analyzed: the scenario of the catchingup development, the scenario of the opened national innovative system, the scenario of creation of the innovative environment, the scenario of local technological leadership. By results of the analysis the need of replacement of model of the catching-up development by model of the innovative modernization capable to provide competitive advantages and innovative break in the conditions of globalization is proved from the theoretical point of view. On this basis the methodical principles of implementation of innovative modernization, such as selectivity are formulated (as limitation of a range of coverage by innovative modernization of branches of economy); independence (as ability to rely in innovative modernization on the national forces and opportunities); complexity (interrelation of technical and technological and organizational and economic aspects of innovative modernization). The crucial role of high-tech and knowledge-intensive industries in innovative updating of all other branches of the domestic industry and implementation of strategy of innovative break in Russia is defined and proved. The interrelation and interconditionality of branches of the high-tech services and branches making the knowledge-intensive production which is for branches of services not only a material basis, but also the animator of growth of economy in general are shown on the example of branch of the aviation industry and branch of air transportation. In the conclusion of work methodological bases of management of innovative modernization of high-tech and knowledgeintensive industries of economy of Russia in their interrelation and interconditionality providing sequence and interrelation of scenario forecasting of development of the Russian social and economic system, strategic priorities, strategic and program and target planning, reproduction of resources, competitiveness of innovative production, technical and technological and institutional providing, and also an efficiency assessment are created. Within this methodology expediency of application of the scenario of local technological leadership is proved and the most acceptable option of strategic planning for realization of strategy of innovative modernization is defined.